The voice of Newfoundland : a social history of the Broadcasting Corporation of Newfoundland, 1939-1949 - Webb, Jeff A. (Jeffrey Allison), 1962- (University of Toronto Press, 2008)
The Voice of Newfoundland studies cultural and political changes in Newfoundland from 1939 to 1949 by taking a close look at the Broadcasting Corporation of Newfoundland's radio programming and the responses of their listeners.